Preparation and characterization of crystal nanocellulose/polyvinyl alcohol (CNC/PVA) film from rice straw - Nor Umi Binti Mohd Yasin (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Food packaging is protecting food from outside and damage to ensure the quality of food for consumers. Food packaging from conventional plastics is widely used in industrial application today. A high determination to produce eco-friendly polymer has leaded the researcher to investigate the biodegradable polymers by adding natural polymers into non-degradable plastics material. Polyvinyl alcohol (PVA) is a material that produced by incorporating the filler into the natural polymers such as crystal nanocellulose (CNC). Therefore in this research, an attempt was made by incorporating natural polymer which is CNC into PVA matrix. This study investigated the influences of different CNC content ranging from 2 to 10 wt%. Apart from that, another technique to induce biodegradation is added by natural pro-oxidant which is spear grass powder into the film. Soil burial test were performed for 1 month to determine the ability of this polymer to degrade this film. As a result, CNC/PVA/Spear grass powder showed higher tensile strength and elongation at break (Eb) compared to CNC/PVA films. However after soil burial test, the tensile strength and Eb of CNC/PVA/Spear grass powder decreases compare to CNC/PVA. Scanning electron microscopy (SEM) micrographs showed rough and coarse for both film. The FTIR results prove that the hemicelluloses and lignin break down after undergoes several pre-treatment. In general, it was found that biodegradable film from CNC/PVA is a potential eco-friendly polymer that can replace non-degradable plastics materials. The addition of spear grass powder as pro-oxidant into the CNC/PVA film increased the degradation rate of the film.